2021
DOI: 10.1186/s13006-020-00347-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between breastfeeding and new mothers’ sleep: a unique Australian time use study

Abstract: Background Infant sleep is of great interest to new parents. There is ongoing debate about whether infants fed with breastmilk substitutes sleep longer than those exclusively or partially breastfed, but what does this mean for the mother? What expectations are realistic for mothers desiring to exclusively breastfeed as recommended by health authorities? There are both biological and social influences on infant and maternal sleep. More accurate information on average maternal sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…The percentage of mothers experiencing insufficient sleep postpartum was significantly higher than before pregnancy. Similar results were found in a study, which concluded that exclusive breastfeeding is associated with reduced maternal sleep duration (average 7.08 h daily) ( 2 ). Another study found that breastfeeding was associated with a slight decrease in maternal sleep satisfaction, with both parents experiencing long-term effects on sleep due to the arrival of new family members ( 40 ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The percentage of mothers experiencing insufficient sleep postpartum was significantly higher than before pregnancy. Similar results were found in a study, which concluded that exclusive breastfeeding is associated with reduced maternal sleep duration (average 7.08 h daily) ( 2 ). Another study found that breastfeeding was associated with a slight decrease in maternal sleep satisfaction, with both parents experiencing long-term effects on sleep due to the arrival of new family members ( 40 ).…”
Section: Discussionsupporting
confidence: 89%
“…Public opinion and even some professionals believe that mothers lack sleep because they need to feed their babies and that using formula would help improve the situation ( 2 , 4 , 15 , 41 ). However, other studies hold different views ( 4 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Breastfeeding dials infants down during the night, to make nightwaking manageable. Excessive night-waking is not caused by frequent flexible feeds, 42 but by disruptions to the biological sleep regulators 25,[29][30][31]33,34,43 Breastfed infants cannot be overfed It's not necessary to wait for cues to offer a feed, knowing that the infant will communicate if not interested. Underlying clinical problems need to be addressed 31 Never coerce at the breast Coercion may result in conditioned dialling up at breast 23…”
Section: Clinical Strategy Ndc Rationalementioning
confidence: 99%
“…The results of research on the quality and length of nocturnal sleep among nursing mothers are inconsistent. While many authors indicate that breastfeeding mothers have a better quality and longer duration of uninterrupted sleep (4,18,19) , other researchers report no differences between breastfeeding and formula-feeding mothers in that respect (20,21) . The lack of consistency in the results is probably due to heterogeneous methodology, various lengths of time elapsed from childbirth and differences in study group characteristics.…”
Section: Epworth Sleepiness Scale (Ess)mentioning
confidence: 99%